Isolation and identification of kaempferol from jangkang (Homalocladium platycladum (F. Muell) Bailey) leaves and its antibacterial activity - Maulita Cut Nuria; Wahyono .; Ratna Asmah Susidarti (Indonesian Journal of Pharmacy, 2011)
Isolation and  identification  of  kaempferol  from  jangkang  (Homalocladium platycladum (F.  Muell)  Bailey)  leaves  and  its  activity  against  B.  subtilis ATCC 9466 dan S. typhi ATCC 1408 has been done. The dried ground leaves (300.04 gram)  were  macerated  with  petroleum  ether,  chloroform  and  methanol respectively.  The  methanol  extract  was  the  most  active  extract  against  both bacteria.  Further  separations  of  this  extract  using preparative  thin  layer chromatography  yielded  flavonoid  glycoside.  Its  aglicon  was  identified  as kaempferol  based  on  its  spectroscopic  data  (MS,  IR, and  UV-Vis)  and  UV spectrum  (densitometry).  This  compound  shows  iradical  zone  of  6.62  mm (Bacillus  subtilis)  and  6.27  mm  (Salmonella  typhi)  at  concentration  of  200 µg/disk.Key words : kaempferol, jangkang, glycoside, aglicon